PENGARUH PENGETAHUAN PASAR MODAL SYARIAH DAN MODAL MINIMAL TERHADAP MINAT BERINVESTASI SAHAM (Studi Kasus Mahasiswa FEBI UIN Jambi) - Sadad Sadad; Hansen Rusliani; Mohammad Orinaldi (Program Studi Manajemen Keuangan Syariah, 2022)
This study aims to determine the effect of Islamic capital market knowledge and minimum capital on interest in investing in shares of FEBI UIN STS Jambi students. The research method is quantitative, and the method of data analysis is the coefficient of determination test. The research sample was 92 samples of FEBI UIN STS Jambi students from the 2018-2019 class, using a Likert scale questionnaire. The results showed that Islamic capital market knowledge (X1) had a significant positive effect on interest in investing in shares (Y), which means Ho is rejected and Ha is accepted. Minimum investment capital (X2) shows that there is a significant positive effect on interest in stock investment (Y), which means Ha is accepted and Ho is rejected. X1 and X2 have a significant effect on the Y variable. It is known that the significance value (X1) and (X2) simultaneously has an effect on (Y) of 0.000 < 0.005 and the value of Fcount > Ftable (60.279 > 3.099). Then the keyword is Ha is accepted and Ho is rejected. This shows that the higher the knowledge of the Islamic capital market and the minimum affordable capital, the higher the interest of students to invest.